Self-Regulation Skills in The Learning Climate of Traditional Muslim Schools in Indonesia - Mukni’ah Mukni’ah; Agus Fawait (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: To develop learning in traditional Muslim schools, this research describes the conditions of learning that develop among traditional Muslim schools; this research aims to reveal, analyze, and find the main ideas of learning theory based on the self-regulation ability of traditional Muslim school students. Method: This research uses a qualitative approach, while this type of research is phenomenological. Determination of informants in this study using purposive sampling were selected as informants in this study were 15 students; in this case, students were interviewed using SRLIS. Data were collected through interviews, direct observation, diaries, video recordings, photography, and artifact analysis. Results: The results of this study show that students' self-regulation abilities in traditional Muslim schools are more group-based. They use the community to develop themselves; group self-regulation skills are dominant among traditional Muslim school students. Novelty: This research shows the self-regulation of traditional Muslim School Students as actors for themselves. The way they learn is through group self-regulation. So, what is new from this research is Group-Based Self-Regulation.